2018
DOI: 10.1111/ases.12672
|View full text |Cite
|
Sign up to set email alerts
|

Objective assessment of robotic suturing skills with a new computerized system: A step forward in the training of robotic surgeons

Abstract: Introduction The purpose of this study was to assess robot‐assisted suturing skills on a laparoscopic intestinal anastomosis model by using a novel computerized objective assessment system. Methods This study compared the suturing skills of 13 surgically naïve participants on an artificial intestinal anastomosis model that mimics real tissue. Each examinee sutured using da Vinci robot assistance under 2‐D and 3‐D visualization and with conventional laparoscopy (CL). Pressure‐measuring and image‐processing devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In addition, the operating handle of the apparatus has tactile feedback, which will be of help during suturing and cutting. It has been reported that 3D vision was significantly faster than the two-dimensional (2D) vision available during da Vinci-assisted surgery [10], and 3D vision may help to perform the surgical operation more easily. The surgeon takes a seat where an adjustment is possible for perfect positioning and chooses an erect posture.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the operating handle of the apparatus has tactile feedback, which will be of help during suturing and cutting. It has been reported that 3D vision was significantly faster than the two-dimensional (2D) vision available during da Vinci-assisted surgery [10], and 3D vision may help to perform the surgical operation more easily. The surgeon takes a seat where an adjustment is possible for perfect positioning and chooses an erect posture.…”
Section: Discussionmentioning
confidence: 99%
“…This is an objective and quantitative assessment system that examines the performance of suture ligature methods in an arti cial intestinal anastomosis model that utilizes four layers: mucosal, submucosal, muscle, and serosal. These intestinal suture sheets simulate human tissue, enabling quantitative assessments of performance time, air pressure leak volume, suture tension, number of fullthickness sutures, and wound opening area [21][22][23]. Each parameter received a score of up to 5 points, with a maximum total score of 25 points.…”
Section: Surgical Tasks and Protocolmentioning
confidence: 99%